Population Dynamics of Maize Stem Borer, Chilo partellus Swinhoe in Upper Himalayas of Jammu Region (Journal of Bio-Science, 2009)
Key words: Population, stem borer and natural enemies DOI:10.3329/jbs.v16i0.3758 J. bio-sci. 16: 137-138, 2008